A mouse intracerebral infection with Neisseria gonorrhoeae. Issue 1 (February 1975) - Diena, B B; Ryan, A; Ashton, F E; Wallace, R; Perry, M B; Daoust, V
Abstract : An intracerebral challenge of HPB black mice with Neisseria gonorrhoeae is described. In this mode, the mice died from 1 to 6 days after challenge, and T1 organisms were obtained up to the fifth day from brain, liver, kidney, and spleen. Experimental gonococcal vaccines gave good protection against the challenge.